1997
DOI: 10.1007/bf03161978
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics of organometallic compounds using μSR

Abstract: Abstraet. The potential of ~tSR in the investigation of molecular dynamics of organometallic compounds is illustrated with applications to the classic metallocene compound, ferrocene. Muonium addition gives two radicals in this case with the slowly relaxing radical showing a repolarisation curve corresponding to a hypertlne field of ca. 200 G suggesting addition to the cyclopentadienyl ring. The temperature dependence of the relaxation of this radical gives an activation energy of ca. 5.4 kJ/mol, in good agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…The theory, however, is fairly well understood, 9,10 and studies have been made of the intramolecular dynamics of radicals formed by muonium addition to Ph 4 X (X D C, Si, Ge, Pb), 11 and to some metallocenes and benzene-metal complexes, 12 in which the muon acts as a spin probe of torsional motion of the phenyl groups and of the overall motion of the cyclopentadienyl or benzene ring about the metal atom.…”
Section: Longitudinal Field Muon Spin Relaxation (Lf-musrx) Measurementsmentioning
confidence: 99%
“…The theory, however, is fairly well understood, 9,10 and studies have been made of the intramolecular dynamics of radicals formed by muonium addition to Ph 4 X (X D C, Si, Ge, Pb), 11 and to some metallocenes and benzene-metal complexes, 12 in which the muon acts as a spin probe of torsional motion of the phenyl groups and of the overall motion of the cyclopentadienyl or benzene ring about the metal atom.…”
Section: Longitudinal Field Muon Spin Relaxation (Lf-musrx) Measurementsmentioning
confidence: 99%
“…In addition to the interest in studying hydrocarbon radicals per se, the MuSR approach may be considered as a 'spin-labelling' technique, but one which is particularly appropriate to small molecules, since overall it is merely the addition of this tiny hydrogen atom which provides the spin label, as opposed to the conventional approach of adding a stable 'nitroxide' function, 6 which is as large as benzene itself, and far exceeds being a minor perturbation of the system. Seemingly unconnected are MuSR (R D relaxation measurements of internal molecular motion in radicals, 7,8 specifically rotation of the benzene rings in tetraphenyllead and its group 4 homologues (and in benzene chromium tricarbonyl), and of the cyclopentadienyl rings in metallocenes. The basis of the relaxation method (LFMuSRx) is that when a molecular motional frequency approaches that of the dominant spectral transition in the muon-electron coupled system, there is an increase in the relaxation rate ( ) of the muon spins, as measured in a longitudinal magnetic field (LF), which reaches a maximum when the frequencies are equal.…”
mentioning
confidence: 99%
“…Ferrocene undergoes a phase transition at 163.9 K 16. During the present series of studies this phase change was observed to show substantial hysteresis 17. X‐ray crystal structure determinations at 295 and 173 K18 show the high temperature phase (HT) to be monoclinic, space group P 2 1 / a with Z =2.…”
Section: Resultsmentioning
confidence: 62%
“…The plot of initial asymmetry against the applied field for the slow‐relaxing component showed a repolarization field of about 20 mT, a value close to that observed for muoniated benzene,1, 23 which would suggest assignment to a cyclopentadienyl ring adduct. At an applied field of 200 mT the temperature dependence of the LF‐μSR relaxation rate of this slower relaxing component has a maximum around 225 K. This was shown17 to be due to an Arrhenius process with an activation energy of about 5.39 kJ mol −1 and an attempt frequency of 1.03×10 12 s −1 . This process is assigned by comparison with NMR14 and QENS15 data to the cyclopentadienyl ring rotation of ferrocene in the room temperature phase (see Table 2)…”
Section: Resultsmentioning
confidence: 91%